Inflammation and Hypertension: Are There Regional Differences? - Patricio López-Jaramillo; Carlos Velandia-Carrillo; Julie Álvarez-Camacho; Daniel Dylan Cohen; Tatiana Sánchez-Solano; Gabriela Castillo-López (International Journal of Hypertension)
Hypertension is a chronic disease with global prevalence and incidence rapidly increasing in low and medium income countries. The surveillance of cardiovascular risk factors, such as hypertension, is a global health priority in order to estimate the burden and trends, to appropriately direct resources, and to measure the effect of interventions. We propose here that the adoption of Western lifestyles in low and middle incomes countries has dramatically increased the prevalence of abdominal obesity, which is the main source of proinflammatory cytokines, and that the vascular systemic inflammation produced by adipose tissue contributes to the development of hypertension. The concentration of proinflammatory cytokines is higher in the Latin American population than that reported in developed countries, suggesting a higher susceptibility to develop systemic low-degree inflammation at a given level of abdominal obesity. These particularities are important to be considered when planning resources for health care programs. Moreover, studying these singularities may provide a better understanding of the causes of the burden of cardiovascular risk factors and the remarkable variability in the prevalence of these medical conditions within and between countries.